Strange School Stories - Packard, Mary; Nang Chan Yeema (New York. USA Scholastic Book Services, 2004)
In strange school stories, you'll get the scoop on some of the world's most odd-inary students, nutty professors, wacky studies, and much, much more!
Keywords: Young Adult